TEKNIK KONSELING “ KURSI KOSONG ” UNTUK MENGURANGI TINGKAT STRES PERKULIAHAN YANG MEMICU PENYALAHGUNAAN NARKOBA - Ayu Jingga Arisa; Nurina Dzawata Samcha; Choiril Ibadiyah Fikri; Noor Avia Ratnawati; Wiryo Nuryono; Devi Ratnasari (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2026)
The "Empty Chair" counseling technique is a method in Gestalt therapy designed to help individuals feel and understand hidden emotions. The aim of this research is to share how effective the "Empty Chair" technique is in reducing the level of stress experienced by students due to academic pressure, which can lead to drug referral behavior. Through a qualitative descriptive approach, data was obtained through counseling interviews. Research findings show that this technique is successful in increasing students' self-awareness regarding the negative emotions they feel, so that they can manage stress in a more positive way. In conclusion, the "Empty Chair" technique can be a preventive way to reduce the possibility of the spread of drugs among students.